2017
DOI: 10.1007/s11356-017-9079-1
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of wastewater containing pharmaceuticals in microcosm constructed wetlands: the occurrence of integrons (int1–2) and associated resistance genes (sul1–3, qacEΔ1)

Abstract: The aim of this study was to analyze the occurrence of sulfonamide resistance genes (sul1–3) and other genetic elements as antiseptic resistance gene (qacEΔ1) and class 1 and class 2 integrons (int1–2) in the upper layer of substrate and in the effluent of microcosm constructed wetlands (CWs) treating artificial wastewater containing diclofenac and sulfamethoxazole (SMX), which is a sulfonamide antibiotic. The bacteria in the substrate and in the effluents were equipped with the sul1–2, int1, and qacEΔ1 resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 80 publications
(109 reference statements)
0
11
0
Order By: Relevance
“…Environmental stressors such as antibiotics and heavy metals accumulated in surface soil could promote horizontal gene transfer between foreign and indigenous bacteria [ 38 ]. Other authors suggested [ 67 ] that the survival of rhizospheric bacteria of CWs can be also associated with their increased resistance to various environment stressors.…”
Section: Resultsmentioning
confidence: 99%
“…Environmental stressors such as antibiotics and heavy metals accumulated in surface soil could promote horizontal gene transfer between foreign and indigenous bacteria [ 38 ]. Other authors suggested [ 67 ] that the survival of rhizospheric bacteria of CWs can be also associated with their increased resistance to various environment stressors.…”
Section: Resultsmentioning
confidence: 99%
“…PCR Molecular techniques, such as PCR, can be used to evaluate the efficiency of constructed wetlands (CWs) for removal of particular CECs like ARGs. For example, Nowrotek et al [57] estimated the efficiency of downflow CW, planted with Phalaris arundinacea (read canary grass), for the removal of three ARGs encoding resistance to disinfectants: sul1-3, int2, qacE∆1. The presence of the selected genes was analyzed in: (1) rhizosphere soil of plant seedlings before transfer to the columns; (2) activated sludge that served as an inoculum; (3) tap water that was used to prepare artificially contaminated wastewater; (4) effluents; and (5) upper layer of substrate at different stages of the experiment.…”
Section: Genomics In Improvement and Evaluation Of Ecological Biotechnologies Efficiency-solution Approachmentioning
confidence: 99%
“…Proliferation of ARGs during sequencing batch reactor (SBR) treatment was assessed by Nowrotek et al (2017).…”
mentioning
confidence: 99%
“…One of the main pathways of ARBs and ARGs occurrences in the environment is via the release of wastewater effluent into water bodies (Nowrotek et al, 2017). In effluent samples taken from ten municipal WWTPs in China, higher abundance of sulfonamideresistant bacteria (SRB) than that of tetracycline-resistant bacteria (TRB) were recorded which was likely due to wider use of sulphonamide than tetracycline .…”
mentioning
confidence: 99%
See 1 more Smart Citation